SPECIFIC CHARACTERISTICS OF SPORTS GAMES - A.Mukhidinov; Sh.Tillaev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Team sports games and their organization are important indicators in the field of sports. Team games are important for them in sports.